History of buddhism in Nepalese context (Triyuga Academic Journal, 2025)
In this paper, I will be writing the history of Buddhism in many aspects. I will dig into Nepalibhupa-vamsavali, a fine work by ManikBajracharya and Axel Micheals which is a mythoi-history. I will also be reviewing Swayambhu Purana writing about the origins of Kathmandu valley. Furthermore, I will also describe the role of Licchavis’ and flourish of Buddhism after they got defeated and entered to Nepal Mandala from the mighty Buddhist King Ajatshatru. Moreover, I will also be talking about the visit of Prithvimalla and the war he waged in Kathmandu valley to protect Buddhism. Thus, in this research paper, I will start with the origins of Buddhism in Nepal to the time of Khas Empire which was entirely Buddhist nation with tolerance towards Hinduism and Shamanism which dominated Trans-Himalayan region. With this, I will show affiliation of Buddhism in Nepal in various aspects like mythology and history in Nepal.